2016
DOI: 10.4081/gh.2016.436
|View full text |Cite
|
Sign up to set email alerts
|

Topographic distribution of gastritis in heavy pigs investigated by a geographic information system approach

Abstract: The aim of this paper was to determine the topographic distribution of gastritis lesions in pigs through an open source geographic information system (GIS) software analysis. The stomachs of 146 Italian heavy pigs were collected at slaughter and subjected to macroscopic pathological examination of the internal mucosa. A total of 623 lesions were either classified as hyperplastic or follicular (97%) with the remaining minority of lesions categorised as atrophic and simple. The hyperplastic gastritis lesions had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…It has been confirmed that GISs can successfully be used for topographic analyses of animal diseases, to create maps of lesion type and distribution on the animal's body. GISs have previously been used to study spinal disc herniation in dogs (Daraban et al, 2014), nodular skin lesions and their malignancy in dogs (Pascotto, Tomè, Comazzi, Marco, & Cornegliani, 2014), gastric lesions in pigs (Pascotto, Capraro, Tomè, & Spanghero, 2016) and the corporal distribution of Ctenocephalides felis felis and C. canis fleas in dogs (Rinaldi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that GISs can successfully be used for topographic analyses of animal diseases, to create maps of lesion type and distribution on the animal's body. GISs have previously been used to study spinal disc herniation in dogs (Daraban et al, 2014), nodular skin lesions and their malignancy in dogs (Pascotto, Tomè, Comazzi, Marco, & Cornegliani, 2014), gastric lesions in pigs (Pascotto, Capraro, Tomè, & Spanghero, 2016) and the corporal distribution of Ctenocephalides felis felis and C. canis fleas in dogs (Rinaldi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The repletion of the stomach with coarse material has an impact on the incidence of the damages of the stomach mucosa and the hyperplastic and the follicular gastritis are the more frequent lesions in heavy pigs with a prevalent localisation in the fundic and pyloric areas (Pascotto et al 2016). In the present trial, we observed a tendency to increase the hyperplastic gastritis in pigs fed the CS diet and this could be interpreted as a reaction of the mucosa to the presence of coarse materials in the gastric contents.…”
Section: Fattening and Slaughter Trial (Exp 2)mentioning
confidence: 99%